2004
DOI: 10.1111/j.1464-5491.2004.01200.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and urinary vascular endothelial growth factor and diabetic nephropathy in Type 2 diabetes mellitus

Abstract: Urinary excretion of VEGF increased during the earlier stage of diabetic nephropathy and was significantly correlated with urinary albumin excretion. This suggests that urinary VEGF might be used as a sensitive marker of diabetic nephropathy and for predicting disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
2
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 29 publications
(22 reference statements)
5
44
2
2
Order By: Relevance
“…It was reported that overproduction of VEGF can act as a link between MAU and cardiovascular risk, which not only increases vascular permeability, promoting haemorrhagic and atherosclerotic processes, but also increases the permeability of the glomerular filter for albumin [14]. Several authors have shown that serum VEGF depends on the degree of obesity [15]; our studies have also revealed this pattern.…”
Section: Fundingsupporting
confidence: 68%
“…It was reported that overproduction of VEGF can act as a link between MAU and cardiovascular risk, which not only increases vascular permeability, promoting haemorrhagic and atherosclerotic processes, but also increases the permeability of the glomerular filter for albumin [14]. Several authors have shown that serum VEGF depends on the degree of obesity [15]; our studies have also revealed this pattern.…”
Section: Fundingsupporting
confidence: 68%
“…131,132 Since podocyte dysfunction occurs in diabetes mellitus and DN is actually considered a podocytopathy, nephrinuria has been reported in some T1DM patients before the onset of microalbuminuria, 133 as well as in some normoalbuminuric T2DM patients. 134 Furthermore, another podocyte biomarker like urinary VEGF has been found to be increased in T2DM patients with microalbuminuria and macroalbuminuria, 135 while higher levels of podocalyxin were seen in diabetic patients with microalbuminuria than in diabetic patients with normoalbuminuria. 136 Finally, some authors have reported that high values of urinary AGEs were seen in 50% of the T2DM patients with normoalbuminuria and in 85% of those with microalbuminuria.…”
Section: Miscellaneous Biomarkersmentioning
confidence: 99%
“…This diminishes the level of an antioxidant enzyme SOD, the first metallo protein enzyme, which is involved in the conversion of super oxide anion radical (O 2 -) to H 2 O 2 thereby removing the superoxide anions. Also the production of VEGF leads to the proteinuria thereby adding complications to DN [78,79]. On an overall perspective, it is found that under diabetic conditions, intracellular ROS is elevated due to many converging pathways and finally leads to nephropathic situation by activating an array of diverging signaling cascades (Figure 3).…”
Section: Oxidative Stress and Diabetic Nephropathymentioning
confidence: 99%